Range Of Motion (ROM) Spherical Grip dapat Meningkatkan Kekuatan Otot Ekstremitas Atas Pasien Stroke - Gina Dwi Anggraini; Septiyanti Septiyanti; Dahrizal Dahrizal (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
Stroke is lost brain function caused by stop his blood supply to the brain. As a result of the disruption of oxygen to the brain needs can occur the clinical manifestations included the weakness of some or all of the body limbs, one of over ekstremities so that the patient could not doing the activity because of the limbs weakness and they needs exercise for preveting disability. Objective is Know the effect of Range Of Motion (ROM) Spherical Grip on muscle strenght of upper extremity on stroke patients. The research used quasi-experimental with pretest and posttest with control group. The population in this study is all stroke patients in the neurological specialist RSUD dr. M. Yunus of Bengkulu City. The Sampling technique used is Cluster Sampling. The number of sample is 32. Instruments used for manual muscle testing. Test for normality using the Kolmogorov-Smirnov and analysis techniques using Wilcoxon Signed Ranks Test and Mann-Whitney with 95% confidence level ( = 0,05). Muscle strenght of the finger mean in the control group 2,44 increase to 2,63 with the difference 0,1875. In the intervention group mean 2,44 increase to 3,13 with the difference 0,6875. Muscle strenght of the wrist mean in the control group 2,38 increase to 2,56 with the difference 0,1875. In the intervention group mean 2,25 increase to 3,00 with the difference 0,75. The result obtained p-value 0,011 finger hand and p-value 0,027 wrist. Exercise Range Of Motion (ROM) Spherical Grip is effective in increase muscle strenght of over extremities on stroke patients.